In Situ Determination of the Water Content of Ionic Liquids. Issue 5 (1st January 2018) - Wippermann, K.; Giffin, J.; Korte, C.
Abstract : This study examines the applicability of electrochemical methods to the in situ determination of the water content in proton-conducting ionic liquids (PILs). Two proton-conducting ionic liquids with different acidities and hygroscopicities of the cations, sulfoethylmethylammonium trifluoromethanesulfonate, [2-Sema][TfO] and N, N-diethylmethylammonium trifluoromethanesulfonate, [Dema][TfO], were used. At first, PIL water electrolytes with known water concentrations ([2-Sema][TfO]: 0.64-6.1 wt%, [Dema][TfO]: 0.18-99.5 wt%) were prepared. Then, the influence of the water content on the electrochemical properties, namely the electrical conductivity, charge of hydrogen oxidation, charge of Pt oxide reduction and onset potential of Pt oxidation, were investigated. The four parameters were plotted as a function of the water concentration and fitted by exponential, linear or asymptotic functions. These fits serve as calibration curves that can be used to determine the actual water concentration by measuring one or more of the four parameters investigated. It was found that the measurement of specific ion conductivity is a fast and simple method across a wide range of water concentrations. The evaluation of the Pt oxide reduction charge from cyclic voltammograms is more time-consuming, but provides higher accuracy at low water concentrations, although the accuracy also depends on the nature of the ionic liquid.